2017
DOI: 10.1002/ange.201706649
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Biomimicry of Artificial Spider Silk Spinning Assessed by NMR Spectroscopy

Abstract: Biomimetic spinning of artificial spider silk requires that the terminal domains of designed minispidroins undergo specific structural changes in concert with the b-sheet conversion of the repetitive region. Herein, we combine solution and solid-state NMR methods to probe domain-specific structural changes in the NT2RepCT minispidroin, which allows us to assess the degree of biomimicry of artificial silk spinning.I na ddition, we showt hat the structural effects of post-spinning procedures can be examined. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“… 44 NT2RepCT in solution also forms assemblies of 4–6 molecules, which are around 7–11 nm in diameter. 29 , 30 In this study, we observed that the shear viscosity at 1 s –1 of NT2RepCT ( Figure 1 A), or the consistency index from fitting the Herschel–Bulkley model ( Figure 2 C) correlated with the concentration. This suggests that the NT2RepCT micelles interact, and in line with this, increased concentration of NT2RepCT leads to increased viscosity of the dope.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“… 44 NT2RepCT in solution also forms assemblies of 4–6 molecules, which are around 7–11 nm in diameter. 29 , 30 In this study, we observed that the shear viscosity at 1 s –1 of NT2RepCT ( Figure 1 A), or the consistency index from fitting the Herschel–Bulkley model ( Figure 2 C) correlated with the concentration. This suggests that the NT2RepCT micelles interact, and in line with this, increased concentration of NT2RepCT leads to increased viscosity of the dope.…”
Section: Discussionsupporting
confidence: 50%
“… 8 , 46 , 48 , 53 56 By using CD spectroscopy, we found that NT2RepCT is mainly in an α-helical conformation at pH 8.0, 7.0, and 6.5 ( Figure 4 A, B and Figure S3B ), which is expected from the α-helical terminal domains and predicted α-helical conformation of the poly alanine regions, and also in line with previous findings where NT2RepCT was studied by NMR spectroscopy. 30 The extreme solubility of NT2RepCT enabled us to study this protein in solution by FTIR spectroscopy, which confirmed that, even at high concentrations, the protein conformation was dominated by α-helical and β-turn components ( Figure 5 ). Previous FTIR spectroscopy studies on gland content also suggested the presence of α-helices accompanied by unidentified secondary structures.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…4E). This is particularly 40 shows that the fusion protein is located in inclusion bodies. A representative example from two repeats is shown.…”
Section: Fibril Formation Mediated By An Exposed Amyloidogenic Sequence Does Not Results In Global Nt Aggregationmentioning
confidence: 90%
“… 12 Expression and purification of spidroins under benign conditions, as well as subsequent biomimetic spinning protocols, have been developed and shown to recapitulate important events of the assembly process. 13 16 However, the mechanical properties of fibers produced in this manner are still inferior to those of the native silk fiber, likely due to the small size of the spidroins used; hence, there is a need for novel ideas on how to produce high-performance spider silk replicas using biotechnological tools.…”
Section: Introductionmentioning
confidence: 99%